Effects of hydromagnetic and chemical reaction over a stagnation point flow of horizontal stretching/shrinking cylinder in Ag-CuO/water hybrid nanofluid - Aladdin, Nur Adilah Liyana; Bachok, Norfifah (Emerald Publishing, 2022)
Purpose: This paper aims to explore on stagnation point flow of Ag-CuO/water over a horizontal stretching/shrinking cylinder by adding the effect of chemical reaction, B together with the magnetic field, M. Design/methodology/approach: A set of reduced ordinary differential equations from the governing equations of partial differential equations is obtained through similarities requirements. The resulting equations are solved using bvp4c in MATLAB2019a. The impact of various physical parameters such as curvature parameter, (Formula presented.), chemical reaction rate, B, magnetic field, M and Schmidt numbers, Sc on shear stress, (Formula presented.) local heat flux, (Formula presented.) and mass transfer, (Formula presented.) also for velocity, (Formula presented.), temperature, θ(η) and concentration, ∅(η) profiles have been plotted and briefly discussed. In this work, some vital characteristics such as local skin friction, (Formula presented.), local Nusselt number, (Formula presented.) and local Sherwood number, (Formula presented.) are chosen for physical and numerical analysis. Findings: The findings expose that the duality of solutions appears in a shrinking region ((Formula presented.) < 0). The value of skin friction, heat transfer rate and mass transfer rate reduction for existing of M, but in contrary result obtain for larger ϒ, B and Sc. Furthermore, the hybrid nanofluid demonstrates better heat transfer compared to nanofluid. Practical implications: The hybrid nanofluid has widened its applications such as in electronic cooling, manufacturing, automotive, heat exchanger, solar energy, heat pipes and biomedical, as their efficiency in the heat transfer field is better compared to nanofluid. Originality/value: The findings on stagnation point flow of Ag-CuO/water over a horizontal stretching/shrinking cylinder with the effect of chemical reaction, B and magnetic field, M is new and the originality is preserved for the benefits of future researchers.